2009
DOI: 10.1111/j.1567-1364.2009.00557.x
|View full text |Cite
|
Sign up to set email alerts
|

Zinc starvation induces a stress response inSaccharomyces cerevisiae that is mediated by the Msn2p and Msn4p transcriptional activators

Abstract: During the production of wine and beer, the yeast Saccharomyces cerevisiae can encounter an environment that is deficient in zinc, resulting in a 'sluggish' or a 'stuck' ferment. It has been shown that the Zap1p-transcription factor induces the expression of a regulon in response to zinc deficiency; however, it was evident that a separate regulon was also activated during zinc deficiency in a Zap1p-independent manner. This study discovered the Msn2p and Msn4p (Msn2/4p) transcriptional activator proteins to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…A previous report suggested that stress response genes may be activated by zinc deficiency via the Msn2/4 transcription factors (31). To determine whether either Msn2/Msn4 or the heat shock factor Hsf1 play a role in regulating UBI4 in response to zinc supply, we generated an allele in which the Hsf1 binding site (HSE) was deleted from the UBI4 promoter (ubi4 HSEmut ).…”
Section: Reduction Of Proteasome Activity Suppresses the Ubi4⌬mentioning
confidence: 99%
“…A previous report suggested that stress response genes may be activated by zinc deficiency via the Msn2/4 transcription factors (31). To determine whether either Msn2/Msn4 or the heat shock factor Hsf1 play a role in regulating UBI4 in response to zinc supply, we generated an allele in which the Hsf1 binding site (HSE) was deleted from the UBI4 promoter (ubi4 HSEmut ).…”
Section: Reduction Of Proteasome Activity Suppresses the Ubi4⌬mentioning
confidence: 99%
“…Furthermore, several stress-responsive genes were also upregulated in surplus iron at 4 h, such as HSP12, HOR7, LSP1, SOD2, GRX4, CCC1, GSY1, and HSP31. In particular, HSP12, HOR7, SOD2, CCC1 and HSP31 contain a stress response element (STRE) consensus sequence in their promoter regions, and all are target genes of the stress-resistant transcription factors Msn2/4 (Gauci et al, 2009;Martinez-Pastor et al, 1996). For instance, Hsp12 is a plasma membrane protein induced by stress conditions that probably initially perceives extracellular surplus iron.…”
Section: Transcriptional Profiles Of Yeast In Response To Surplus Ironmentioning
confidence: 99%
“…The vacuolar iron transporter Ccc1 that is induced by Msn2/4 facilitates the storage of surplus intracellular iron in the vacuole to alleviate high-iron toxicity. In addition to Msn2/4-dependent stress-responsive genes, many upregulated genes in other metabolic pathways are also targets of Msn2/4 (Table 1) (Gauci et al, 2009). Therefore, we further checked changes in the transcription of MSN2/4, with the result that MSN4 increased 1.5-fold and 1.75-fold under 5 mM of Fe 3+ at 1 and 4 h, respectively, compared to the stable transcription of MSN2 in iron-surplus conditions.…”
Section: Transcriptional Profiles Of Yeast In Response To Surplus Ironmentioning
confidence: 99%
“…41 Table 2 lists DEGs which are reported to be controlled via the stress responsive element (STRE) in S. cerevisiae. 41,42 As shown in Table 2, quite a few stress-responsive genes were down-regulated under the stress of multiple inhibitors, such as HXK1, GPH, TDH1, TDH3, PGM, CTT1 etc., while there were also some genes up-regulated such as SSA3, SOD2, TDH2, HSP26, HSP31, ALD, MDH2 etc. Our RNA-seq results showed that there was only MSN2 in K. marxianus and with no signicant change under the multiple inhibitors condition (data not shown), indicating that this MSN2 might be different to that in S. cerevisiae.…”
Section: Msn2/4 Mediated Stre Related Degsmentioning
confidence: 99%
“…K. marxianus YHJ010 was precultivated in 5 ml of YPD medium at 42 C overnight. Then the cells were transferred into 500 ml Erlenmeyer asks containing 100 ml of the YPD medium with or without mixed inhibitors containing 0.…”
Section: Samples Preparation and Transcriptome Analysismentioning
confidence: 99%